Preparation and Characterization of 1-Halobenzimidazoles - Ramkumar, B. (Asian Journal of Chemistry, 2010)
Two new N-halo compounds have been introduced. Preparation of 1-halobenzimidazoles and their characterization by spectral and electrochemical methods have been discussed.